Dioxin Exposure Alters Molecular and Morphological Responses to Thyroid Hormone in Xenopus laevis Cultured Cells and Prometamorphic Tadpoles. (9th October 2017) - Taft, Justin D; Colonnetta, Megan M; Schafer, Rachel E; Plick, Natalie; Powell, Wade H
Abstract: Amphibian metamorphosis is driven by thyroid hormone (TH). We used prometamorphic tadpoles and a cell line of the African clawed frog ( Xenopus laevis ) to examine immediate effects of dioxin exposure on TH. Gene expression patterns suggest cross-talk between the thyroid hormone receptor (TR) and aryl hydrocarbon receptor (AHR) signaling pathways. In XLK-WG cells, expression of Cytochrome P450 1A6 ( cyp1A6 ), an AHR target, was induced 1000-fold by 100 nM TCDD (2, 3, 7, 8 tetrachlorodibenzo- p -dioxin). Krüppel-Like Factor 9 ( klf9 ), the first gene induced in a cascade of TH responses tied to metamorphosis, was upregulated over 5-fold by 50 nM triiodothyronine (T3) and 2-fold by dioxin. Co-exposure to T3 and TCDD boosted both responses, further inducing cyp1A6 by 75% and klf9 about 60%. Additional canonical targets of each receptor, including trβa and trβb (TR) and udpgt1a (AHR) responded similarly. Induction of TH targets by TCDD in XLK-WG cells predicts that exposure could speed metamorphosis. We tested this hypothesis in two remodeling events: tail resorption and hind limb growth. Resorption of ex vivo cultured tails was accelerated by 10 nM T3, while a modest increase in resorption by 100 nM TCDD lacked statistical significance. Hind limbs doubled in length over four days following 1 nM T3 treatment, but limb length was unaffected by 100 nM TCDD. TCDD co-exposure reduced the T3 effect by nearly 40%, despite TCDD induction of klf9 in whole tadpoles, alone or with T3. These results suggest that tissue-specific TCDD effects limit or reverse the increased metamorphosis rate predicted by klf9 induction.